2020
DOI: 10.1021/acs.est.0c04532
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Dynamics in Attached and Suspended Bacterial Communities in Three Drinking Water Distribution Systems with Variable Biological Stability

Abstract: Microbial presence and regrowth in drinking water distribution systems (DWDSs) is routinely monitored to assess the biological stability of drinking water without a residual disinfectant, but the conventional microbiological culture methods currently used target only a very small fraction of the complete DWDS microbiome. Here, we sequenced 16S rRNA gene amplicons to elucidate the attached and suspended prokaryotic community dynamics within three nonchlorinated DWDSs with variable regrowth conditions distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 78 publications
(148 reference statements)
0
7
1
Order By: Relevance
“…In addition, no significant linear correlations were found between ambient temperature and both Shannon and Inverse Simpson diversity indices of the water samples (p > 0.05) (Table 1). By contrast, previous studies found clear seasonal variations in bacterial communities of cold drinking water (McCoy and VanBriesen, 2012;Henne et al, 2013;Pinto et al, 2014;Prest et al, 2016b;Vavourakis et al, 2020). We hypothesize that the lack of clear seasonal variations in bacterial communities in the current study could be because the HPS simulator delivered temperature-stable tap and shower water to the bathroom.…”
Section: Limitations and Future Researchcontrasting
confidence: 93%
See 2 more Smart Citations
“…In addition, no significant linear correlations were found between ambient temperature and both Shannon and Inverse Simpson diversity indices of the water samples (p > 0.05) (Table 1). By contrast, previous studies found clear seasonal variations in bacterial communities of cold drinking water (McCoy and VanBriesen, 2012;Henne et al, 2013;Pinto et al, 2014;Prest et al, 2016b;Vavourakis et al, 2020). We hypothesize that the lack of clear seasonal variations in bacterial communities in the current study could be because the HPS simulator delivered temperature-stable tap and shower water to the bathroom.…”
Section: Limitations and Future Researchcontrasting
confidence: 93%
“…Mycobacteriaceae contains a single genus Mycobacterium which is an important drinking water opportunistic pathogen (Good, 1985;Marciano-Cabral et al, 2010;Lu et al, 2017;Wang et al, 2019;Zhang and Lu, 2021). For both cold and hot tap water, the relative abundance of Burkholderiaceae (one dominant family in drinking water and PPSs) (Zeng et al, 2013;Buse et al, 2014;Ferro et al, 2019;Vavourakis et al, 2020) and Xanthobacteraceae (associated with nitrogen fixation) (Oren, 2014) obviously dropped in the second draws (compared with the first draws) (Figure 3). By contrast, the relative abundance of Azospirillaceae (associated with nitrogen fixation) (Sridevi et al, 2012), Obscuribacterales_fa, Moraxellaceae (contains potentially opportunistic pathogens) (Pettersson et al, 1998;Inkinen et al, 2018), and Hyphomonadaceae (contains "strict aerobic and stalked and non-stalked species") (Abraham and Rohde, 2014) significantly increased in the second draws for both cold and hot tap water.…”
Section: The Bacterial Community Compositions Of Cold Tap Hot Tap and Shower Water Were Distinctmentioning
confidence: 99%
See 1 more Smart Citation
“…From the collected water samples, a maximum of 1000 ml was filtered through a polycarbonate membrane filter with a 0.2 µm pore size (Track-etch membrane, Sartorius, The Netherlands). Filters were stored at − 20 • C until further DNA extraction and 16S rRNA amplicon sequencing, which was done as described previously (Vavourakis et al, 2020). Negative controls (water samples of DNase/RNase free water) and positive controls (Zymo DNA mock communities) were also added during filtration and subsequent DNA extraction.…”
Section: Microbial Community Analysismentioning
confidence: 99%
“…Factors influencing the drinking water microbiome are site specific due to the unique type and combination of treatment technologies across DWTPs and DWDS configurations, source water types, and operational practices. Thus, while the impact of individual treatment process or environmental conditions on the drinking water microbiome may be compared across DWTPs and DWDSs, it is often impossible to perform a paired comparison between drinking water systems due to the inability to control for the type and sequential combination of treatment and distribution practices. For instance, studies have investigated drinking water microbiome dynamics in multiple DWTPs that use similar treatment processes but utilize different source waters or utilize the same source water but different treatment approaches and/or disinfection residual free systems. In addition, often such comparisons are limited to either the treatment system or the distribution system but rarely encompass a comprehensive source-to-tap analysis. To the best of our knowledge, no study has yet investigated the impact of identical drinking water treatment regimens and similar distribution practices on the drinking water microbiome in the same full-scale systems utilizing similar source waters.…”
Section: Introductionmentioning
confidence: 99%